MicroRNAs regulating autophagy: opportunities in treating neurodegenerative diseases - Mohseni, Mahdi; Behzad, Ghazal; Farhadi, Arezoo; Behroozi, Javad; Mohseni, Hamraz; Valipour, Behnaz (Frontiers in Neuroscience, 2024)
Neurodegenerative diseases (NDs) are increasingly prevalent in our aging population, imposing significant social and economic burdens. Currently, most ND patients receive only symptomatic treatment due to limited understanding of their underlying causes. Consequently, there is a pressing need for comprehensive research into the pathological mechanisms of NDs by both researchers and clinicians. Autophagy, a cellular mechanism responsible for maintaining cellular equilibrium by removing dysfunctional organelles and misfolded proteins, plays a vital role in cell health and is implicated in various diseases. MicroRNAs (miRNAs) exert influence on autophagy and hold promise for treating these diseases. These small oligonucleotides bind to the 3’-untranslated region (UTR) of target mRNAs, leading to mRNA silencing, degradation, or translation blockade. This review explores recent findings on the regulation of autophagy and autophagy-related genes by different miRNAs in various pathological conditions, including neurodegeneration and inflammation-related diseases. The recognition of miRNAs as key regulators of autophagy in human diseases has spurred investigations into pharmacological compounds and traditional medicines targeting these miRNAs in disease models. This has catalyzed a new wave of therapeutic interventions aimed at modulating autophagy.